2014
DOI: 10.1111/joor.12205
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of CAD/CAM fit restoration evaluations

Abstract: The evolution and development of CAD/CAM systems have led to the production of prosthetic reconstructions by going beyond the use of traditional techniques. Precision adjustment of prosthetic elements is considered essential to ensure sustainable restoration and dental preparation. The purpose of this article was to summarise the current literature on the fitting quality of fixed prostheses obtained by CAD/CAM technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
155
2
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(207 citation statements)
references
References 161 publications
23
155
2
11
Order By: Relevance
“…The clinically allowable marginal gaps of dental prostheses have been described in numerous studies. Some authors have reported marginal gaps under 120 µm to be clinically allowable for traditional fixed prostheses 13. Others have reported marginal gaps of 160 - 172 µm to be clinically acceptable for conventional crowns, with an acceptable marginal gap range of under 200 µm and occlusal gap range of under 250 - 300 µm 23242526.…”
Section: Discussionmentioning
confidence: 99%
“…The clinically allowable marginal gaps of dental prostheses have been described in numerous studies. Some authors have reported marginal gaps under 120 µm to be clinically allowable for traditional fixed prostheses 13. Others have reported marginal gaps of 160 - 172 µm to be clinically acceptable for conventional crowns, with an acceptable marginal gap range of under 200 µm and occlusal gap range of under 250 - 300 µm 23242526.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, other studies have underlined the superiority of adaptation of crowns created using optical impressions compared to those using conventional impressions 7121314151617. As an indirect CAD/CAM technique, conventional impressions are transmitted to a prosthetist who then conducts the digital acquisition of the data, by scanning either the impression or the model itself.…”
Section: Discussionmentioning
confidence: 99%
“…Several dental researchers have reportedd that the clinically acceptable marginal gap for cast restorations is less than 160 µm. [1415] Larger marginal gap leads to dissolution of luting cement and subsequent periodontal and caries disease activities. The results of this study are in agreement with the findings of Davis et al .…”
Section: Discussionmentioning
confidence: 99%